Asian place, Filipino nation a global intellectual history of the Philippine Revolution, 1887-1912 - CuUnjieng Aboitiz, Nicole (Columbia studies in international and global history, 2020)
This book reassesses the thought and impact of the Philippine Revolution (1896-1905), particularly in relation to the landscape of "Asia," then newly reconceived in anti-imperial thought. This reassesment explains the Revolution's full historical role and place, illuminating an important transitional moment in Southeast Asian, imperial, and international history in the region, and reconnecting Philippine history to that of Southeast and East Asia at this pivotal moment of the birth of the Philippine nation. There were alternative visions of world order and of modernity, other than those offered by the West, and the legacies of these visions have lived on beyond this transnational moment of political and discursive experimentation"--